Laser sintering of polymer particle pairs studied by in situ visualization. Issue 6 (9th January 2019) - Hejmady, Prakhyat; van Breemen, Lambèrt C. A.; Anderson, Patrick D.; Cardinaels, Ruth
Abstract : The effects of sintering conditions on laser sintering of polymer particle doublets are unraveled by in situ visualization. Abstract : Merging of particle pairs during selective laser sintering (SLS) of polymers is vital in defining the final part properties. Depending on the sintering conditions, polymers can undergo full or partial sintering whereby incomplete sintering results in poor mechanical properties. At present, the underlying mechanisms and related conditions leading to various consolidation phenomena of polymer particles are not well understood. In the present work, a novel in-house developed experimental setup is used to perform laser sintering experiments on polystyrene (PS) particle doublets while performing in situ visualization of the sintering dynamics. From the recorded images, the evolution of the growth of the neck radius formed between both particles is analyzed as a function of time. Sintering conditions such as heating chamber temperature, laser pulse energy and duration, laser spot size and particle size are precisely controlled and systematically varied. A non-isothermal viscous sintering model is developed that allows qualitative prediction of the observed effects of the various parameters. It is shown that the sintering kinetics is determined by a complex interplay between the transient rheology caused by the finite relaxation times of the polymer and the time-dependent temperature profile which also affects the polymer viscosity. The combination of a full material characterization with sintering experiments under well-defined conditions has resulted in a general understanding of the effects of material and process parameters on laser sintering. Thereby a strong foundation is laid for the route towards rational design of laser sintering.